Implementasi Program Golden Moral untuk Membentuk Generasi Khairu Ummah bagi Santri TPQ Pelangi Nusantara - Azizah, Agtika Yasyfa Nur; Agustin, Ayu Tri; Dewi, Dyah Mustika Chandra; Anisa, Mutiara Nur; Azizah, Zahroh Nur; Wicaksono, Anggit (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
TPQ Pelangi Nusantara has several issues, including the absence of a standardized curriculum, limited teaching staff, and lack of parental involvement in children's character education. As a solution, the Golden Moral program is implemented by adjusting the principles of golden habits, a concept that emphasizes the formation of good habits in daily life. The program aims to improve children's morals and the quality of TPQ education through various activities such as program socialization and distribution of supporting books, Qur'an and Iqro reading and writing training, and strengthening speaking skills through speech training. In addition, there is also literacy corner (pojok literasi), worship education (wudhu, tayamum, salat), game-literasi (garasi), and creation event (ajang kreasi). The program runs for four months, from August to November 2023. This program succeeded in changing the behavior of students to be better and have a positive character and succeeded in improving the quality of learning in TPQ. Santri also experienced an increase in the ability to read and write the Qur'an of the students, the students' understanding of speech materials, worship, and other islamic materials, as well as fostering creativity in their work.